IMPeTUs parameters correlate with clinical features in newly diagnosed multiple myeloma - Shuaishuai Xu; Shengxiu Jiao; Huimin Guo; Wenkun Chen; Shuzhan Yao (European Journal of Radiology Open)
Objectives: To investigate the correlations between IMPeTUs-based 18 F-FDG PET/CT parameters and clinical features in patients with newly diagnosed multiple myeloma (MM). Materials and methods: PET/CT were analysed according to the IMPeTUs criteria. We correlated these PET/CT parameters with known clinically relevant features, bone marrow plasma cell (BMPC) infiltration rate and the presence of cytogenetic abnormalities. Results: A total of 149 patients (86 males, 63 females; mean age, 59.9 ± 9.7 years) were included. Bone marrow metabolic state correlated with the most clinical features including hemoglobin (rho=-0.23, p=0.004), FLC ratio (rho=0.24, p=0.005), β2 M (rho=0.28, p=0.001), CRP (rho=0.25, p=0.003), serum calcium (rho=0.22, p=0.02), serum creatinine (rho=0.24, p=0.004) and BMPC (rho=0.21, p=0.003). Besides, the level of hemoglobin was significant lower (0.043), and the levels of FLC ratio (0.037), β2 M (p=0.024), CRP (p=0.05), and BMPC (p=0.043) were significant higher in patients having hypermetabolism in limbs and ribs. Hottest bone lesion Deauville criteria had a moderate correlation with CRP (rho=0.27, p=0.001) and serum calcium (rho=0.25, p=0.01). Conclusion: Several IMPeTUs-based PET/CT parameters showed significant correlations with clinical features reflecting disease burden and biology, suggesting that these new criteria can be used in the risk stratification in MM patients.